Evolution Of Acquisition Of Land In Malaysia: Accommodating Sustainable Development And Humanity Fairness - Ahmad Hamidi Mohamed; Nurul Majdiah Mohamad Sayuti; Noorfajri Ismail; Kamilah Wati Mohd (GAE (Global Academic Excellence), 2025)
Land is very important for public and private ownership. Public ownership needs land for development and the provision of public amenities and infrastructure to the people. Meanwhile, private ownership is critical for people's wellness. However, compulsory land acquisition in Malaysia plays an important role in the development of the country's public infrastructure and amenities while considering private ownership. In order to support development goals and approaches, land acquisition laws and frameworks must change overtime. Different methods ofdevelopment and technological advancements necessitate the creation of specific laws to handle the development process. This study uses a qualitative methodology to examine how Malaysian land acquisition laws have changed over time, taking into account all of the changes made to the Land Acquisition Act 1960 [Act 486]. The study's key conclusions include how the current land acquisition laws are dynamic and adaptable to different development strategies while maintaining the public interest. However, it is suggested that in order to provide the legal framework, it must go above and beyond in predicting the future development strategy